COMPARATIVE STUDY OF STRUCTURE PERFORMANCE WITH AND WITHOUT BASE ISOLATION SYSTEM USING DOUBLE FRICTION PENDULUM SYSTEM ON REINFORCED CONCRETE BUILDING - Bahana Utama, Bagus
Important buildings such as hospitals, power generator facilities and other important public facilities that must remain operational when an earthquake occurs are one of the consideration for conducting research and development of new alternative methods. Base isolation system with the type of double friction pendulum system (DFPS) is one of the new innovations with the aim of disaster mitigation. The purpose of this study is to compare the performance of structure with and without DFPS at maximum earthquake conditions and to study the effect of stiffness variations and friction coefficient variations from DFPS. Five office building models, ten story tall, with dual system structure which is located in Jakarta with medium soil condition. Seven earthquake data were used with nonlinear time history analysis (NLTHA). The parameters to be compared are structural performance such as the top floor acceleration, base shear, story drift, performance level, dissipation energy and maximum deformation of the DFPS